About Teachers, Shamans and Healers: Towards an Ethics of Violence in Legal Education - Saucier Calderón, Jean-Paul (2015)
This article discusses how legal education extends the symbolic violence intrinsic to the law and legal discourse. The article, while keeping in mind power relations inherent to legal education, discusses how disciplinary approaches reinforce the symbolic violence conveyed through legal education. The article presents «Interdisciplinarity» in contrast to a structuring and compartmentalized view of the law, and explains how interdisciplinarity can attenuate symbolic violence in legal education. Having this in mind, the author proposes an «ethics of violence» in legal education that suggests professors should moderate the levels of symbolic violence channeled during the educational process and participate in the unveiling of symbolic violence-generating structures. The article concludes with views on the limits of such an ethical proposition, particularly when considering how an ethics of violence could end up legitimizing the issues it initially sought to oppose.